Do female chief financial officers and female directors cooperate? Evidence from investment efficiency - Ismail, I.; Abdul Wahab, Effiezal (2024)
Purpose: This paper aims to examine whether the cooperation between female chief financial officers (CFO) and the proportion of female directors would impact investment efficiency. The investigation is grounded in the increasing number of female top managers globally and the notion that female tends to cooperate more with other female than with male. Design/methodology/approach: This study uses publicly listed firms in Bursa Malaysia from 2016 to 2020, which yielded a sample of 2,022 firm-year observations. The authors used multivariate ordinary least square regression to test the relationship, and to correct for the selection bias, the Heckman selection and PSM test were used. Findings: The authors find a positive relationship between female CFOs and investment efficiency. A higher proportion of female directors accentuates this result. The findings support the homophily argument that similar characteristics (gender) promote cooperation. This shows that cooperation between female CFOs and directors improves investment efficiency. The results suggest that the improvement in investment efficiency could relate to higher managerial discretion for female CFOs and their ability to collaborate with female directors. These results are robust to a series of additional endogeneity tests. The findings have important implications for policymakers and firms to encourage more appointments of females in top management positions. Originality/value: By highlighting the cooperation between female CFOs and female directors, this study contributes to the understanding that cooperation among females improves investment efficiency.